Improving the Quality of English Learning in Madrasah Tsanawiyah Muhammadiyah 10 Wukir at Wangen Using Lolly-Pop Card Media - Riskha Aprilia Listianingrum; Dwi Yuliarti; Indah Yani (OJS Universitas Muhammadiyah Gresik, 2018)
The primary purpose of this article is to improve the quality of English learning process at MTs Muhammadiyah 10 Wukir by using Lolly-Pop Card media which is expected to make students more interested in learning English. In improving the quality of the learning process of English, the author also provides training in the making of learning media in the form of Lolly-pop Card. Participants who follow this English learning activity amounted to 6 people including formal educators. The results obtained after the training show that by using Lolly-pop Card media, the quality of English learning done by the teacher is better because it can improve the ability of learners in teaching activities and learners are more interested in learning English in the classroom. This is evidenced by the results of tests given after using Lolly-pop Card media. They are also more interested in learning to use Lollypop Card media so that the process of teaching and learning in the classroom is more active, fun, and not dull.